STRATEGI KOMUNIKASI PROMOSI PARIWISATA PULAU PANDANG OLEH DINAS PARIWISATA KABUPATEN BATU BARA - Wahyu Utama; Syahrul Abidin; Muhammad Faisal (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
This study aims to determine the promotional strategy of the tourism office in making Pandang Island a tourist destination in Batu Bara Regency. This research is a qualitative study with descriptive methods. In this study the researcher acts as an observer and systematically records the symptoms / phenomena / objects under study. The results of this study show that the promotion strategy of the Tourism Office in making Pandang Island a tourist destination is with 5 promotional mixes that are used, namely through Advertising in the form of brochures, banners, electronic media, websites and applications. Personal Selling (face-to-face sales), namely by holding exhibitions or exhibitions outside the region and direct marketing (direct marketing) by word of mouth marketing or through stories of experience, influencing factors in efforts to increase tourist visits, tourism in Batu Bara Regency is widely known, especially the island of view where tourists who come are not only local but also foreign countries. Communication barriers faced by the Batu Bara Regency Tourism Office in promoting the island of view, namely, the community has not been able to provide comfort and security to visitors or tourists on the island of view, especially when tourist vehicles are parked in the port area and human resources (HR) are still lacking in understanding the language when there are tourists from abroad who come.